The Use Of Hybrid Teaching To Teach English In Vocational High School - Fathyah Rahmaniah (English Language Education Study Program of STKIP PGRI Banjarmasin, 2022)
This paper describes the implementation of Hybrid Teaching which has just been applied to Vocational High School students in Yogyakarta. This paper also explains how the Hybrid teaching system is a combination of online learning and face-to-face learning. To explain further, in this paper there are two comparisons between Hybrid Teaching and Online Teaching where the two teaching methods are related to each other. The comparison includes the advantages and disadvantages of the two teaching methods, both in terms of material and the impact of the two teaching methods.